Diversity of the sponge fauna associated with white coral banks from two Sardinian canyons (Mediterranean Sea). (12th November 2019) - Bertolino, M.; Ricci, S.; Canese, S.; Cau, A.; Bavestrello, G.; Pansini, M.; Bo, M.
Abstract: The three-dimensional coral scaffolds formed by the skeletons of the cold-water corals Madrepora oculata and Lophelia pertusa represent an important deep-sea hard substratum and create an optimal shelter for a rich associated fauna in which the contribution of Porifera has still not been fully considered. The taxonomic analysis of sponges collected from two Sardinian canyons (Nora and Coda Cavallo, 256–408 m) and associated with the dead coral matrix resulted in 28 species, including new records for the Mediterranean Sea, Italian fauna or Central Tyrrhenian Sea. In addition, for many species this is the first finding associated with the coral framework or the first documentation of the in situ morphology. The taxonomic comparison with sponge assemblages associated with coral frameworks from Santa Maria di Leuca, Strait of Sicily and Bari Canyon, gave the opportunity to evaluate the similarities among geographically separated banks. Overall, the percentage of exclusive species (recorded only in one site), is very high (81%) and only one species is shared by all four sites, suggesting a low connectivity among the sponge communities. The percentage of shared species is higher for the Maltese community, supporting the role of the Sicily Channel as a crossroads between the communities of the eastern and western Mediterranean basins. Here, 55% of the sponges associated to the coral framework are also reported in shallow-water coralligenous assemblages, indicating a high bathymetric connectivity as well as an ecological plasticity allowing these species to occupy a wide range of small, dark refuges.